Limite superior e inferior de retenção da água no solo : método laboratorial e de estimativa - Santos, Deborah de Amorim Teixeira (2022)
The upper and lower limits of water for the plants have been identified as field capacity when the soil is at the voltage of 10 or 33 kPa and the permanent wilting point at the voltage of 1,500 kPa. To obtain these values quickly, pedotransfer functions emerged, which use data from physical attributes to estimate soil moisture. There are several functions developed in the literature, but its use requires care, so that an estimate that is not close to the real one had not occurred. Therefore, the objective was to compare the values estimated by the pedotransfer functions with the data of soil water retention limits observed in the laboratory. Seven areas located in the state of Mato Grosso were selected, totaling 126 soil samples collected. For the soil physical attributes, soil density, total porosity, macro and micropores, organic matter and curve points at stresses of 6, 10, 33 and 1,500 kPa were analyzed. The results obtained from the analyses were used to evaluate the functions of Lal (1979), Oliveira et al. (2002), Giarola et al. (2002), Nascimento et al. (2010), Rosseti et al. (2022) and a Software developed by Saxton et al. (2006). For the evaluation, pearson coefficient (r), mean error (MS), square root of mean error (RMSE), agreement index (d) and performance index (c) were used. The function that presented the best performance for the estimated result for field capacity was rosseti et al. (2022), and for the permanent wilting point the function of Giarola et al. (2002). It is concluded that pedotransfer functions are able to estimate the data of soil water retention limits, however they cannot be extrapolated, so that the accuracy of the results is not compromised.